The Role of Entrepreneurs at the Cooperative Service in the Development of Tempe SMEs - Robby Ilham Prakoso, Racmad; Rodiyah, Isnaini (Universitas Muhammadiyah Sidoarjo, 2022)
The role played by the Cooperatives and UMKM Service in Sidoarjo Regency for business actors, the tempeh sector in Sepande Village, only provides a soybean skin peeler tool, and the Cooperative Service itself is said lacking in socialization to kopti Karya Mulya because Kopti is less open to the Cooperative Service of Sidoarjo. Using qualitative descriptive writing and research locations in Sidoarjo Regency Cooperative Office, for the informants the Head of the Cooperative and Service, Head of Kopti Karya Mulya and members of Kopti Karya Mulya. Collecting data obtained by interview, observation and documentation, the data analysis technique uses model methods such as data collection, data reduction, data presentation and drawing conclusions. Based on the results of the study, the role of the Cooperative Service as an entrepreneur in marketing tempeh is still less than optimal. Because members who are elderly are less knowledgeable about technology.